Adaptabilidade e estabilidade de variedades de mandioca (manihot esculenta crantz) nos municípios de Labrea e Manaus, AM - Costa, Evandro Inacio da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
In Amazonas state (Brazil) there are a lot of manioc landraces which are mainly consumed as flour. For improve this species, the best and easiest strategy is to test them in different Amazonian locations. This work aimed to evaluate the adaptability and stability of seven bitter manioc landraces. From Lábrea were chosen Cobiçada, Minerva and Flecha-amarela, and from Manaus Mana, Trairinha, Nanica and Jurará. In each local was adopted randomized block design, with seven treatments and four replications, with eight plants perplot. The evaluated characteristics were: plant height, stem diameter; root number, pulp color, yield and dry matter; and aerial mass. The GxE analyses revealed there to be interaction only for root diameter, number and yield, and plant height. And the adaptability and stability analyses of root yield showed Jurará landrace was unstable, yet it was the most adapted to both locations. In Lábrea and Manaus Jurará yield, respectively: 43.7 and 26.5 t ha -1 of roots;39.8 and 43.7 t ha -1 of aerial mass; 10.8 and 4.8 roots per plant and 331.7 and 316.6 cm of plant height. Therefore, the Jurará should be tested in elsewhere of Amazon.